SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TANAMAN PANGAN MENGGUNAKAN METODE MULTI ATTRIBUTE UTILITY THEORY - Yulianti, Eva; Putri, Mega Mardiana; Syahrani, Anna; Swara, Ganda Yoga (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Food crops are one of the basic human needs such as rice, corn, beans, tubers and others. One of the well-known staple foods is corn. Corn (Zea mays L.) is one of the most important food crops besides wheat and rice. As the main source of carbohydrates in several regions of Indonesia, rice is also able to produce rice which is the staple food of the community. The problem of crop failure generally occurs because farmers do not pay close attention to the condition of the soil, because not all plants are in accordance with the soil conditions in an area. Due to the selection of food crops that are not suitable, it will not get optimal results. With these problems, a decision support system was built. which can help farmers to choose which plants are suitable to be planted so that they get optimal results. This study uses the method of Multi Attribute Utility Theory. The Multi Attribute Utility Theory method is used to calculate the assessment in determining food crops that match many criteria, namely land, temperature, rainfall, humidity, drainage, salinity. This system can determine which crop yields are more suitable for planting in Kota Pariaman by getting the highest value results where this value will determine which plants are more suitable to be planted so that they get good results, and can also provide recommendations to farmers in making decisions before planting. ie with the yield of rice plants get a value of 0.7 and for corn 0.2 then the highest yield is rice plants.Keywords: Decision Support System, Multi Attribute Utility Theory, Food Crops.